Semar Sandy-app: monitoring system for sandy soil irrigation based on android application. Issue 1 (January 2021) - Arifin, I; Herawati, A; Mujiyo, Sumani; Widijanto, H
Abstract: Indonesia's population increase leads to increase in food needs. The increasing need for food requires national food security. However the country faces the problem of agricultural land diminishing. Sandy soil is one of the suboptimal land that can be used for agricultural cultivation. Sandy soil leads to problems such as low water-holding capacity that will result in low levels of soil moisture. Soil moisture content is a very important factor in plant growth. Accordingly, we need an alternative solution to solve the problem. One of technology used in agriculture is an irrigation system. Therefore, the author proposes an idea in forms of Semar Sandy-App. Semar Sandy-App is a monitoring system as well as a system that provides direct supply water in the plant root zone. The system uses subsurface drip irrigation with perforated pipes then water comes out of the hole to wet the soil. This system can be a solution to optimize sandy soil through efficiency and effectiveness in providing water. The system can control and monitor the plant water requirements through the use of microcontroller that is connected directly to the android system, so it will increase agricultural productivity to support the availability of food for the community.